Diseño y construcción de un prototipo de sismógrafo digital con comunicación celular para el I2TEC de la Universidad Nacional de Loja. - Granda Morales, Daniel Alejandro (2023)
The following project consisted of the development and implementation of a prototype of a digital seismograph with communication to the cellular network for monitoring seismic events through a web page, such prototype alerts (notifies) through an SMS message when an earthquake is detected. The prototype can be divided into two fundamental parts, the computer part called Software and the physical part called Hardware. The hardware represents the electronic components interconnected to each other for the detection of seismic waves of the digital seismograph. The elements that compose the hardware of the prototype are: accelerometer that detects the seismic movements that occur; mini UPS to supply power in case of power outage; a Raspberry Pi that executes the algorithms of detection and categorization of telluric events and its Wi-Fi card that performs the communication with the Web page and also allows sending the SMS alert through the Twilio API, thanks to this Wi-Fi card the communication between the hardware located in the I2TEC laboratories of the UNL and the web page that can be accessed through a QR code implemented on the cover of the prototype can be performed. The web page will store the seismic events detected by the seismograph with their characteristics such as: date, time, duration, intensity, magnitude, and location of the seismograph. To achieve the characteristics of the Web server, the programming languages JavaScript, HTML 5 markup language and CSS style language were used. For the development of the detection and categorization of seismic events was done with the help of Python 3. Finally, the digital seismograph with cellular communication was installed in the facilities of the National University of Loja in the laboratory of technological developments of the I2TEC. Keywords: Seismograph, accelerometer, datalogger, Richter Scale, Mercalli Scale, Seismic acceleration.